The Definition of the Time-Space and Power Performances of the Ultrawideband Antennas - Zamyatin, V.I.; Yermakov, G.V. (Радиофизика и радиоастрономия, 2002)
The definitions of the time-space, frequency−space and power characteristics of the ultrawideband antenna systems permitting to evaluate from unified positions the overall performance of different function videopulse radiotechnic systems are given.